Exposición aguda a partículas de contaminación ambiental: función cardíaca, estrés oxidativo y mecanismos de respuesta inflamatoria sistémica - Marchini, Timoteo (2015)
The exposure to environmental particulate matter (PM) is associated with increased cardiovascular morbidity and mortality rates. Oxidative stress and inflammation have been suggested to play a central role. However, the underlying mechanisms are poorly understood. The aim of this work was to evaluate this hypothesis in acute models of exposure to a combustion-derived PM surrogate (ROFA), by different in vivo and in vitro approaches. Heart oxidative and energetic metabolism was altered in ROFA-exposed mice, as well as mitochondrial function and cardiac contractile and diastolic reserve. Increased levels of oxidative stress and inflammation markers were also found in ROFA-exposed mice, together with intravascular polymorphonuclear leukocytes activation. ROFA-induced systemic inflammation promoted leukocyte trafficking, by the activation of endothelial and myeloid cells. Monocyte depletion prevented local and systemic inflammation, while in vivo TNF-? blockage reduced ROFA-induced cardiac alterations. These findings indicate that oxidative stress and inflammation are triggered by the exposure to PM, which might be associated to the observed cardiovascular alterations reported after PM inhalation.